Effects of Shorebirds on Dispersal and Growth of Algae in Connecticut. - Proctor, Noble Stoneman (Thesis Ph. D.--Univ. of Connecticut., 1976)
Keywords: Connecticut; Algae as food; Algal blooms; Algae; Growth; Shore birds; dept.bio; faculty_collection

A strain of Serratia marcescens pathogenic for larvae of Lymantria dispar: Infectivity and mechanisms of pathogenicity - Podgwaite, J.D.; Cosenza, B.J. (Journal of Invertebrate Pathology, 1976)
The ED50 of a strain of Serratia marcescens for microinjected instar III and IV gypsy moth larvae was 7.5 and 14.5 viable cells, respectively. Percentage and rate of mortality were found to be highly variable among replicates of the same instar and between instars in free-feeding bioassays. Mortality in second instar larvae occurred before ecdysis, whereas practically no mortality occurred in third and fourth instars until the molting period. Neither Boivin endotoxin preparations nor culture filtrates were toxic to instar III larvae when administered per os or by microinjection. Histological evidence indicated that the microorganism invaded the hemocoel of healthy or predisposed insects through the gut wall. The rapid multiplication of the bacterium in the hemocoel of infected insects, followed by death in the absence of extensive tissue damage, indicated mortality was due to a septicemia. The histological and biological evidence presented indicated that the microorganism would be less than effective if utilized as a conventional microbial insecticide. © 1976.
Keywords: dept.bio

A strain of Serratia marcescens pathogenic for larvae of Lymantria dispar: Characterization - Podgwaite, John D; Cosenza, B J (Journal of Invertebrate Pathology, 1976)
A gram-negative bacillus, pathogenic for gypsy moth larvae, was characterized culturally, morphologically, and physiologically as a member of the Serratia group of the family Enterobacteriaceae. The microorganism lacked the pigmentation characteristic of the group but was generally distinguished from closely related members of the family by its inability to produce gas from glucose, inositol, glycerol, and cellobiose; its rapid liquefaction of gelatin; and its failure to ferment raffinose or arabinose. The microorganism displayed lecithinase, deoxyribonuclease, and chitinase activity. The percentage of G + C in DNA from this bacterium was within the range reported for known strains of Serratia marcescens. © 1976.
Keywords: dept.bio